2020
DOI: 10.1161/atvbaha.119.313633
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-144 Silencing Protects Against Atherosclerosis in Male, but Not Female Mice

Abstract: Objective: Atherosclerosis is a leading cause of death in developed countries. MicroRNAs act as fine-tuners of gene expression and have been shown to have important roles in the pathophysiology and progression of atherosclerosis. We, and others, previously demonstrated that microRNA-144 (miR-144) functions to post-transcriptionally regulate ABCA1 (ATP binding cassette transporter A1) and plasma HDL (high-density lipoprotein) cholesterol levels. Here, we explore how miR-144 inhibition may protect ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…In addition, studies in tissue-specific FXR deficient mice showed that hepatic but not intestinal FXR is essential for induction of miR-144 and FXR-dependent hypolipidemia. Interestingly, miR-144 was found to have sex-specific silencing effects [ 55 ]. Finally, miR-148a was found to control in vivo hepatic ABCA1 expression and circulating HDL-C levels, revealing a role for miR-148a as a key regulator of hepatic LDL-C clearance through direct modulation of LDLR expression, and showing the therapeutic potential of miR-148a inhibition to improve the elevated LDL-C/HDL-C ratio, a significant risk factor for cardiovascular disease [ 56 ].…”
Section: Abca1 and Plasma Lipid Levelsmentioning
confidence: 99%
“…In addition, studies in tissue-specific FXR deficient mice showed that hepatic but not intestinal FXR is essential for induction of miR-144 and FXR-dependent hypolipidemia. Interestingly, miR-144 was found to have sex-specific silencing effects [ 55 ]. Finally, miR-148a was found to control in vivo hepatic ABCA1 expression and circulating HDL-C levels, revealing a role for miR-148a as a key regulator of hepatic LDL-C clearance through direct modulation of LDLR expression, and showing the therapeutic potential of miR-148a inhibition to improve the elevated LDL-C/HDL-C ratio, a significant risk factor for cardiovascular disease [ 56 ].…”
Section: Abca1 and Plasma Lipid Levelsmentioning
confidence: 99%
“…A study by Chen et al [ 103 ] concluded that increased plasma level of miR-144 might serve as a promising biomarker for CAD and its severity. This association can be partially explained by the recent research that demonstrated the involvement of miR-144 in cholesterol and oxysterol metabolism in male CAD mice[ 104 ]. Moreover, altered expression of miR-144 was shown to be a risk factor for ischemic stroke in T2DM patients[ 98 ].…”
Section: Epigenetic Mechanisms Involved In Macrovascular Disease In Diabetic Patientsmentioning
confidence: 99%
“…The picture of HDL-C as the "good" cholesterol has eroded. Previous also have indicated that epigenetic changes within the ABCA1 (ATP-binding cassette A1) gene promoter among French-Canadian founder population contribute to the interindividual variability in plasma HDL-C concentrations and are associated with coronary artery disease (CAD) expression with negatively related to HDL-2 phospholipid level and HDL particle size [7], while MicroRNA-144 antagonism in male mice increase circulating HDL cholesterol levels by remodeling the HDL particle, and enhance reverse cholesterol transport through performing an effect with 3 0 -UTR harbours binding sites for miR-33, miR-758, and miR-26 of Cyp7b1 which have been shown to regulate Abca1 and lipid metabolism [8].…”
Section: Introductionmentioning
confidence: 99%